Development of Instagram Media Message Design for Promotion and Sales of Cocopeat and Cocofiber MSMEs - Askia, Fazhira; Novrianti, Novrianti; Zen, Zelhendri; Pratiwi, Rahmi (Universitas Negeri Padang, 2025)
The development of Instagram message design media is motivated by promotional challenges faced by MSME actors, namely the absence of appropriate and attractive promotional media on digital platforms. Until now, the MSMEs have not utilized digital promotional media. This condition has led to low effectiveness in communication and marketing of Cocopeat and Cocofiber products. To address this issue, an Instagram message design was developed to be visual, informative, and persuasive. This study aims to develop an Instagram message design that is valid and practical to be used as an attractive promotional medium.This research employed a Research and Development (R&D) approach using the Four-D (4D) development model, which includes the stages of: (1) Define, (2) Design, (3) Develop, and (4) Disseminate. Data collection instruments used in this study included validation sheets and customer response questionnaires. Product validity was tested by two media experts. The practicality test was aimed at customers of the Cocopeat and Cocofiber MSMEs.The development of the Instagram message design was carried out through the stages of the Four-D development procedure. This process resulted in a promotional media product in the form of Instagram visual message designs that are informative, attractive, and aligned with the characteristics of MSMEs. The product underwent validation by Curriculum and Educational Technology lecturers. The validation results from Media Expert I were categorized as “Very Valid” with an average score of 4.60, and Media Expert II also categorized the product as “Very Valid” with an average score of 4.80. Message Design Expert I assessed it as “Very Valid” with an average of 4.70, and Message Design Expert II gave a score of 4.80. The practicality test results showed an average score of 4.55, categorized as “Very Practical.” Based on these results, it can be concluded that the Instagram message design using the Linktree application for the Cocopeat and Cocofiber MSMEs is considered very valid and very practical.Keywords: Development, Message Design, 4D